Islam dan Nasionalisme: Studi Atas Pergumulan Islam dan Nasionalisme Masa Pergerakan Nasional Indonesia - Hairiyah, Hairiyah (UIN Sunan Kalijaga Yogyakarta, 2022)
Abstract: The discourse of Islam and nationalism became an interesting topic of conversation at the beginning of the 20th century when the Islamic world intersected with the idea of a Western-style nation-state in the Islamic world. The nation-state concept is considered a-historical for Muslim societies. Almost all Muslim countries in the third world, including Indonesia, experience nation-state problems in finding their national identity and character (nation character buildings). Especially in Indonesia, this kind of nation-state problem has sometimes not been completely resolved which in turn will always give rise to the